(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The article describes the research of geobotanists about the transformation of plant cover, measures to increase the diversity of biota in places. Also, scientific information is provided about the negative effects of human factors, production enterprises and techniques on the flora and ways to reduce them.